American citizenship - Lyon, William Otis (My University, 1893)
Introduction: As the United States has just opened to the world the Columbian Exposition in honor of the four hundredth anniversary of the discovery of America by Columbus, it seems fitting that something might be said at this time about the state of American citizenship as it exists in the United States.
Citation: Lyon, William Otis. American citizenship. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Columbia exposition; America; Citizenship; Theses; Manuscripts (documents)